2008
DOI: 10.1111/j.1468-3083.2008.02679.x
|View full text |Cite
|
Sign up to set email alerts
|

Nail psoriasis: a combined treatment with 8% clobetasol nail lacquer and tacalcitol ointment

Abstract: Combined treatment with tacalcitol ointment and 8% clobetasol-17-propionate in a nail lacquer is a safe, effective treatment for nail bed and nail matrix psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 22 publications
(36 reference statements)
0
22
0
1
Order By: Relevance
“…Combined treatment with 8% clobetasol-17-propionate in lacquer applied at the weekend and tacalcitol ointment under occlusion on weekdays for 6 months showed a good and quick response; with 78% improvement in the modified target NAPSI score at the end of therapy along with reduction in nail pain. [71]…”
Section: Treatment Of Nail Psoriasismentioning
confidence: 99%
“…Combined treatment with 8% clobetasol-17-propionate in lacquer applied at the weekend and tacalcitol ointment under occlusion on weekdays for 6 months showed a good and quick response; with 78% improvement in the modified target NAPSI score at the end of therapy along with reduction in nail pain. [71]…”
Section: Treatment Of Nail Psoriasismentioning
confidence: 99%
“…Vitamin D 3 analogues of calcipotriol, calcitriol, and tacalcitol have been used in the treatment of nail psoriasis by inhibiting keratinocyte growth and differentiation and suppressing T-cell activity and cytokine production [1, 7, 21, 33]. In a double-blind study involving 58 patients with nail bed psoriasis, topical application of calcipotriol ointment twice daily was found to be as effective as twice daily application of betamethasone dipropionate in reducing subungual hyperkeratosis after 3–9 months [30].…”
Section: Topical Therapymentioning
confidence: 99%
“…Rigopoulos et al [26] demonstrated that the combined treatment with calcipotriol cream (once daily, 5 days a week) and clobetasol propionate cream (once daily, 2 days a week) for 6 months resulted in a 72% reduction at subungual hyperkeratosis. The synergistic effect of topical vitamin D 3 , which mainly affects the nail bed, togetherwith topical corticosteroid that is more effective on nail matrix, may provide safer and better treatment for nail psoriasis [20, 21, 30]. …”
Section: Topical Therapymentioning
confidence: 99%
“…[62,63] Pulsed dye Laser (PDL) has been used to treat psoriatic plaques, and recently, PDL has been shown to improve nail psoriasis as well. [64] Chronic paronychia is a common problem among the females which is multifactorial in origin.…”
Section: New In Onychomycosis Treatmentmentioning
confidence: 99%